Impacts of House Mice on Sustainable Fodder Storage in Australia - Peter R. Brown; Steve Henry (Agronomy, 2022)
Mice cause substantial economic, social, and environmental damage to rural production systems and communities in Australia, especially during mouse plagues. The losses and damage caused by mice to hay/fodder storage are not well understood, given the size of the industry, so a pilot study (survey of 14 growers) was designed to better understand the physical and economic damage, consider disease implications, and identify the management strategies available. During a mouse plague, mice were regarded as the only factor (other than weather) that affected the long-term sustainability of fodder storage. Growers were feeding fodder to livestock (sheep/cattle) at twice the rate they normally would because of mouse damage and contamination. Mice damaged strings and the structure of bales, making transport impractical, leading to destruction of some stacks. Losses caused by mice were estimated at AUD 140,000 (range = AUD 7000–461,580; equivalent to 30–40% loss of value) and included estimates of physical damage to hay/fodder bales, rodenticides, and labour costs. Growers were concerned about contamination and disease transfer to livestock (and workers) from mice through urine/faeces and their carcasses, especially during mouse plagues. There are significant gaps in our knowledge on the impacts of mice to fodder storage in Australia. Research is needed to (1) identify effective mouse control options, (2) determine the economic impact of mice, and (3) undertake a disease study of mice, to help inform appropriate management strategies for effective control.